2008
DOI: 10.1002/poc.1431
|View full text |Cite
|
Sign up to set email alerts
|

What governs nitrogen configuration in substituted aminophosphines?

Abstract: The trigonal planar geometry of the nitrogen atom in commonly used phosphoramidite ligands is not in line with the traditional valence shell electron pair repulsion (VSEPR) model. In this work, the effects governing nitrogen configuration in several substituted aminophosphines, A 2 PNB 2 (A or B ¼ H, F, Cl, Br, Me, OMe, BINOP), are examined using modern computational analytic tools. The electron delocalization descriptions provided by both electron localization function (ELF) and block localized wavefunction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Alternative ‘(b)’ does not provide clarity for more frequently and readily observed planarization of nitrogen over phosphorus in these types of compounds. Alternative ‘(c)’ appears to have wider scope and hence is more employed nowadays to explain such situations 126. A set of phosphoramidite molecules (‘O 2 NP’ framework) were examined using advanced computational techniques126 and it was concluded that negative hyperconjugation could best explain the observed facts and that the ligands where P is bonded to electron donating groups have never been used in catalysis for obtaining fruitful results.…”
Section: Aminophosphinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative ‘(b)’ does not provide clarity for more frequently and readily observed planarization of nitrogen over phosphorus in these types of compounds. Alternative ‘(c)’ appears to have wider scope and hence is more employed nowadays to explain such situations 126. A set of phosphoramidite molecules (‘O 2 NP’ framework) were examined using advanced computational techniques126 and it was concluded that negative hyperconjugation could best explain the observed facts and that the ligands where P is bonded to electron donating groups have never been used in catalysis for obtaining fruitful results.…”
Section: Aminophosphinesmentioning
confidence: 99%
“…Alternative ‘(c)’ appears to have wider scope and hence is more employed nowadays to explain such situations 126. A set of phosphoramidite molecules (‘O 2 NP’ framework) were examined using advanced computational techniques126 and it was concluded that negative hyperconjugation could best explain the observed facts and that the ligands where P is bonded to electron donating groups have never been used in catalysis for obtaining fruitful results. It was also felt that the fundamental electronic properties of phosphoramidite ligands have to be studied in detail for a much better ligand design.…”
Section: Aminophosphinesmentioning
confidence: 99%
“…The P-N bond is a key segment of the molecule. It is known that the N-atom lone pair can be delocalized on the P-N bond to some extent depending on the electronic nature of the N and P substituents (Wodrich et al, 2009). In the case of PPAs, this n N !…”
Section: Figurementioning
confidence: 99%
“…Thus, the N atom is sp 2 -hybridized, with a nearly trigonal planar geometry. The four substituents of the P and N atoms in (VII) can have orthogonal planar, orthogonal pyramidal or antipyramidal conformations (Mo et al, 1999;Wodrich et al, 2009) (Fig. 2).…”
Section: Figurementioning
confidence: 99%
“…It is known that significant electron donation from the nitrogen lone pair to the amidite phosphorus occurs, resulting in a nearly trigonal-planar molecular geometry of the nitrogen, which is typical of an sp 2 hybridization state-and of an increased P-N bond order, thus the rotation around this bond is restricted. 17 Furthermore, the phosphorus basicity can be finetuned by changing the substituents at the nitrogen, which may have a significant influence on the coordination and steric properties of the ligand and the substrate complexes; hence the catalytic properties can also be fine-tuned. These unique electronic properties prompted us to investigate the N-substituent effect of the ligand in the Rh-catalyzed asymmetric hydrogenation and in the Pd-catalyzed asymmetric allylic alkylation of benchmark substrates.…”
Section: Introductionmentioning
confidence: 99%